Herbaceous and Woody Root Biomass, Seasonal Changes in Root Turnover, and Arbuscular Mycorrhizal and Ectomycorrhizal Colonization during Primary Succession in Post-Mining Sites - Satoshi Kaneda; Petra Zedníková; Jan Frouz (Diversity, 2022)
Seasonal changes in the biomass and length of fine roots and their growth into ingrowth cores were measured in a chronosequence of post-mining sites represented by 6-, 16-, 22-, and 45-year-old study sites, located on spoil heaps after brown coal mining in the Sokolov coal mining district. The depth distribution of roots differed between herbs and woody species and also with succession age. At the 22-year-old site, the greatest root biomass was found in the fermentation layer (248.9 ± 113.4 g m2) and decreased with depth. In the case of herbaceous root biomass, the greatest root biomass was found in the 16-year-old site (63.7 ± 15.2 g m2), again in the fermentation layer, which decreased with depth. Overall root biomass increased with succession age, reaching its highest value in the 45-year-old site. In younger sites, the root biomass was dominated by herbs and grasses, whereas woody roots dominated in older sites. After one year, the root biomass in ingrowth cores reached up to one quarter of in situ biomass, which would suggest a low turnover rate. However, the difference between the minimum and the maximum value during the course of one year represents more than half of the mean value. Analysis of the number of arbuscules on roots of Plantago lanceolata sown in soil from all succession stages revealed extensive colonization by arbuscular mycorrhizal fungi in early succession (14.2 ± 0.3 mm root−1), decreasing with succession age, and reaching the lowest value in the 22-year-old site (2.4 ± 0.08 mm root−1) before increasing in the oldest site. Colonization of roots by ectomycorrhizal fungi increased with succession age, reaching a maximum in the 16-year-old site. In comparison with the extent of ectomycorrhizal colonization in relation to root length, the greatest length of ectomycorrhiza-colonized roots was found in the 22-year-old site; hence, the pattern was the opposite of the one observed in arbuscular mycorrhiza-colonized roots.